Cost-effective analysis on the suitability of photovoltaic pumping systems in Bangladesh - Karim, A.N. Mustafizul; Rahman, Md Mizanur (ELSEVIER, 1993)
With the experience of the global energy crisis attempts are being made throughout the world to harness alternate sources of energy. In this respect photovoltaic (PV) technology stands out as one of the potential alternatives. Though initially its use was restricted to some special purposes,in recent times with the reduction in price of PV modules it has expanded to variety of common uses. In Bangladesh several PV systems have been installed for various common purposes. Initial investment for this technology is very high, while operation and maintenance cost is very low. However, for mass-scale commercial operation this needs to be economically viable compared to its conventional alternatives. In this paper attempt has been made to analyze the cost economics of PV technology dedicated for the purpose of water pumping. It has been found that with the present price level, solar pumping is not economically competitive with the conventional systems. Sensitivity analyses have been performed to identify the limiting conditions under which photovoltaics will be economically suitable. Thus this study provides some guidelines in evaluating the present situation in the context of economic viability and future scopes of photovoltaic technology in Bangladesh.